Systematically Applying UDL to Effective Practices for Students With Learning Disabilities. (August 2018) - Cook, Sara Cothren; Rao, Kavita
Based on the premise that instruction should be designed from the outset to reduce barriers, Universal Design for Learning (UDL) guidelines provide a set of flexible options and scaffolds to ensure access for all learners. Using the UDL framework, teachers and researchers can systematically adapt effective practices that have been established by methodologically sound research studies to have meaningful gains for students with learning disabilities (LD). Specifically, we suggest that teachers can select an effective practice and then use the UDL framework to individualize the practice (while maintaining core components). Furthermore, we propose that researchers may use this approach to (a) clearly define how UDL was applied to a practice and (b) systematically measure the effects of UDL when applied to practices that have been established as effective by methodologically sound research. Although teachers and researchers can apply UDL to effective practices for all students, in this article, we highlight how secondary teachers can design and adapt effective practices for students with LD, who need intensive interventions to improve skills (e.g., reading comprehension, decoding) and access to grade-level curriculum.